Increasing access to health workers in underserved areas: a conceptual framework for measuring results - Huicho, Luis (World Health Organization, 2010)
Many countries have developed strategies to attract and retain qualified health workers in underserved areas, but there is only scarce and weak evidence on their successes or failures. It is difficult to compare lessons and measure results from the few evaluations that are available. Evaluation faces several challenges, including the heterogeneity of the terminology, the complexity of the interventions, the difficulty of assessing the influence of contextual factors, the lack of baseline information, and the need for multi-method and multi-disciplinary approaches for monitoring and evaluation. Moreover, the social, political and economic context in which interventions are designed and implemented is rarely considered in monitoring and evaluating interventions for human resources for health. This paper proposes a conceptual framework that offers a model for monitoring and evaluation of retention interventions taking into account such challenges. The conceptual framework is based on a systems approach and aims to guide the thinking in evaluating an intervention to increase access to health workers in underserved areas, from its design phase through to its results. It also aims to guide the monitoring of interventions through the routine collection of a set of indicators, applicable to the specific context. It suggests that a comprehensive approach needs to be used for the design, implementation, monitoring, evaluation and review of the interventions. The framework is not intended to be prescriptive and can be applied flexibly to each country context. It promotes the use of a common understanding on how attraction and retention interventions work, using a systems perspective.